Knowledge, Attitudes, and Barriers Toward Research Methodology Among Intern Doctors at Misurata University - Salem Shenaisheh; Omar Alhaddad; Alyaa Azzain; Mohammed Ben Saud; Fatima Elsoughier; Habeeba Ahmed; Malak Elgubbi (Khalij-Libya Journal of Dental and Medical Research, 2025)
Research is fundamental to advancing medical science, informing evidence-based clinical practice, and promoting professional growth for newly graduated doctors. However, many intern doctors face barriers such as limited exposure, insufficient time, and inadequate training, which hinder their participation in research activities. The internship period is an ideal time to acquire complex skills, such as research methodology. This study aimed to assess knowledge, attitudes, and perceived barriers to medical research among intern doctors at the Faculty of Medicine, Misurata University. A descriptive cross-sectional survey was conducted among intern doctors at the Faculty of Medicine, Misurata University, Libya. Data were collected from 58 participants (response rate of 74.4%) using a self-administered Google Forms questionnaire. The instrument assessed personal data, knowledge (15 multiple-choice questions), attitude (11 Likert scale statements), and perceived barriers. Knowledge and attitude scores were categorized into Poor/Negative, Moderate/Neutral, and Good/Positive levels. Inferential statistics (t-tests) were used to compare scores across different groups, with a p-value <0.05 considered significant. The mean knowledge score was 6.88±2.82, indicating generally poor knowledge, with 51.7% of participants in the "Poor Knowledge" category. In contrast, the mean attitude score was 41.69±7.34, corresponding to a positive attitude, with 55.2% of participants demonstrating a positive attitude. Key perceived barriers included difficulty in accessing study samples (82.7%), feeling of inadequate statistical skills (81.0%), and lack of time (78.9%). Notably, prior research training and project contribution were associated with significantly more positive attitudes. Intern doctors show a strong, positive attitude toward scientific research but possess poor knowledge of research methodology. Prior exposure to research, such as training and project contribution, is essential for fostering positive attitudes. Recommendations include integrating structured, practical research training into both undergraduate and postgraduate curricula to bridge the significant knowledge gap and address perceived barriers.